Vloga lutkovnega gledališča pri kulturni vzgoji otrok - Šinko, Sabina (Revija za elementarno izobraževanje, 2008)
"Arts for children" are a part of our cultural education but do not yet have aproper place in the school system. They are not properly encouraged or promoted, both in education and culture. This article presents some of the characteristics of children's puppet theater, which is one of the most exposed types of art. Children can get an ongoing education about theatre by regularly visiting quality puppet shows, which is important for understanding esthetics and learning about morals. This is especially important because children receive these great experiences in puppet theatre all the way through puberty. It is also an excellent vehicle for understanding adults through an artistic medium. The article also highlights some guidelines on how children experience puppet shows and why they feel so close to them.
Keywords: kulturna vzgoja; lutkovno gledališče; lutke; child; otroci; animacija